Effects of the Chinese herbal medicine Hong Huang decoction, on myocardial injury in breast cancer patients who underwent anthracycline-based chemotherapy - Cao, Sihan; Xue, Jingxian; Chen, Lu; Hao, Yun; Lu, Meijuan; Feng, Ming; Wang, Huanhuan; Zhou, Jun; Yao, Chang (Frontiers in Cardiovascular Medicine, 2022)
Objective To assess the effects of Hong Huang Decoction (HHD), a Chinese herbal medicine, on myocardial injury in breast cancer patients who underwent anthracycline (ANT)-based chemotherapy. Methods A total of 51 patients with breast cancer who underwent an ANT-based chemotherapy program and met the inclusion/exclusion criteria were allocated to the treatment or placebo groups using a random number generation process. Patients in the treatment group received liquid HHD twice a day. Treatment was given from 1 day prior to chemotherapy up to the end of chemotherapy (after 6 months). Participants in the placebo group received a placebo over the same schedule. Left ventricular ejection fraction (LVEF), global longitudinal strain (GLS), diagnostic markers of acute myocardial infarction [e.g., lactate dehydrogenase (LDH), creatine kinase-MB (CK-MB), and B-type natriuretic peptide (BNP)], nitric oxide (NO), superoxide dismutase (SOD), as well as pro-inflammatory cytokines [e.g., tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and human C-reactive protein (CRP)], and anti-inflammatory cytokine interleukin-10 (IL-10), were outcome measures assessed before chemotherapy, 3 and 6 months after chemotherapy. Results Compared to the placebo group, the GLS value was significantly higher in the treatment group (19.95 ± 1.16 vs. 19.06 ± 1.64, P ≤ 0.001). Significant differences were also noted for levels of SOD (689.71 ± 203.60 vs. 807.88 ± 182.10, P < 0.05), IL-6 (58.04 ± 22.06 vs. 194.20 ± 40.14, P ≤ 0.001), IL-10 (237.90 ± 94.98 vs. 68.81 ± 32.92, P ≤ 0.001), NO (75.05 ± 26.39 vs. 55.83 ± 19.37, P ≤ 0.005), and TNF-α (301.80 ± 134.20 vs. 680.30 ± 199.60, P ≤ 0.001) in the patients before chemotherapy compared to 6 months after initiating chemotherapy. Conclusion HHD regulated the levels of IL-6, IL-10, SOD, NO, and TNF-α. The results demonstrated that GLS is a better indicator of early myocardial injury compared to LVEF, and HHD could modulate oxidative stress to protect against ANT cardio toxicity. Clinical trial registration Chinese Clinical Trial Registry, identifier ChiCTR1900022394. Date of registration: 2019-04-09.